Chemical composition of Pacific manganese nodules and crusts analyzed at Scripps Institution of Oceanography using X-ray emission spectrometry - Fisk, Mary B; Frazer, Jane Z (PANGAEA, 2022)
23 manganese nodules and crusts from 17 sites in the Pacific Ocean were analyzed at Scripps Institution of Oceanography using X-ray emission spectrometry (XES). Samples were ground to < 74 microns, pressed into pellets and dried at 110 Degrees Centigrade. They were analyzed by XES for 1000 seconds.
Keywords: Geochemistry; manganese micronodule; manganese nodule; ocean; sediment